Greenhouse gas investigations in rivers, lakes and oceans - Fietzek, Peer; Esser, Daniel; Kramer, Stefan (2012)
Carbon dioxide (CO2) and methane (CH4) concentrations in rivers, lakes and the oceans are key parameters for addressing many questions arising from both scientific and industrial applications. Extensive greenhouse gas (GHG) datasets are important for reliable climate modelling and the measurement of dissolved CO2 is on the way to becoming a parameter to be continuously monitored by national environmental authorities rather than just by marine chemists. The concentrations of both gases show large spatial and temporal gradients at the sea surface and within the water column. ‘Point measurements' help to understand the underlying processes or form the basis for countermeasures in, for example, industrial applications. Ocean acidification, natural gas seepage, carbon capture and storage (CCS), as well as pipeline and general long-term monitoring, are only a few of the example applications. The offshore oil and gas sector is one of the biggest domains in respect of dissolved gas sensor applications. Dissolved CH4 measurements are important tools within pipeline and subsea structure inspections as only two-thirds of produced hydrocarbons actually reach the consumer with the remaining third being lost during production and transport. The ongoing exploitation of deepwater reservoirs, along with the maintenance of subsea production and processing facilities, entail increased automation featuring the idea of permanent monitoring of dissolved CH4. Additionally, the scientific and environmental interest in both the quality of, and changes within, fresh water reservoirs is steadily increasing.